Innovations in Telemedicine: Implications for the Evolution of Health Professional Practices - Pratap Swain, Mahendra; Teja Suvvada, Harsha; Sewarik, Rupali; Gulfam Shaikh, Raja; Pandurang Dhumale, Sonali (Journal of Neonatal Surgery, 2025)
Background: Telemedicine is now a powerful innovation in healthcare allowing access to services and operational efficiency. But despite this, it still poses barriers to integration in professional practice – technical barriers, ethical concerns, and the requirement for specialised training. The study explores the impact of telemedicine innovations on the health professional practice and attempts to identify the benefits, challenges, and opportunities for improvement. Methods: A mixed methods approach was used: systematic literature review semi-structured interviews with 30 healthcare professionals and a survey of 250 respondents. Qualitative data were analyzed using thematic analysis and statistical analysis of quantitative data identified trends and correlations. Results: It was perceived as a major enabler of improved patient access (85%) and improved efficiency (70%). But technical issues (38%), ethical issues (24%), and increased training needs (65%) were the challenges. Communication strain and the need to reconfigure professional roles to fit digital healthcare delivery were highlighted by participants. Conclusion: Telemedicine has changed the face of healthcare delivery with significant benefits, but comes with changes in professional practice. Its challenges may be addressed by policy reform, technological progress, and a constant stream of education, which unlock its full potential. Future research should investigate how telemedicine may affect clinical outcomes long term and how it may work with new technologies.